The identity of Peliosanthes revoluta and P. torulosa (Asparagaceae) described from Guangxi, and P. pseudorevoluta, a new species also from Guangxi, China - Lin, Nan Xin; Li, Xiao Feng; Zhang, Gao Cheng; Feng, Hui Zhe (Phytotaxa, 2025)
Synonymizing Peliosanthes revoluta under P. torulosa, we attribute their morphological disparities to developmental stages or preservation artifacts. Both taxa share key features, such as purple flowers, nodulose rhizomes, and overlapping flowering periods. However, a newly recognized species, P. pseudoreflexa, differs from P. torulosa in several notable characteristics. P. pseudoreflexa has purplish-red flowers, solitary flowers per bract (vs. multiple in P. torulosa), shorter pedicels (4–6 mm vs. 5–14 mm in P. torulosa), elliptic revolute perianths that do not contact the receptacle (vs. folded margins and contact the receptacle in P. torulosa), and a hexagonal ovary cross-section. Additionally, the new species lacks the basal stalky part of the perianth present in P. torulosa.